Analisa Hubungan Pengelolaan Sampah Terhadap Kejadian Diare di Provinsi Kalimantan Timur - Gita Prajati; Suhenra Maulana (Jurnal Serambi Engineering, 2024)
Household waste that unmanaged well can lead into the emergenceof infectious diseases, like diarrhea. The waste management level in East Kalimantan province increases every year, directly proportional tocases of diarrhea. This research’s aimis to know the relationship between waste managementlevel and cases of diarrheain East Kalimantanprovince. This research using secondary datas analysis as the method. Datas related to waste management and cases of diarrhea are collected from Central Bureau of Statisticsof East Kalimantan and National Waste Management Information System of KLHK. There are six districts/cities as the location ofcollecting the secondary datas, which are Samarinda, Balikpapan, Bontang, Kutai Kertanegara, Paserand Penajam Paser Utara.The datascollected from 2018 to 2022. The data analysis used chi-square. This research showsPaser Districthas the lowest waste management level among the others. Whereas, BontangCityhas the highest waste management level. The Paser Districtalso has the highest cases of diarrhea. The value of asymptoticsignificance (2sided) from the chi-square test (0.129) lower than 0.05, so it can be concluded that Ho were approved. It implicated that there is no relationshipbetween waste management level to cases of diarrhea in the East Kalimantanprovince.